Vietnam : the early decisions - Gardner, Lloyd C., 1934-; Gittinger, Ted (University of Texas Press, 1997)
More than twenty years have passed since American military personnel finally withdrew from Vietnam, yet haunting questions remain about our involvement there. Perhaps the most persistent of these - and certainly the most unanswerable - is the question of what would have happened if President Kennedy had lived beyond 1963. Would he have ended American involvement in Vietnam? For many Americans, Oliver Stone's powerful film JFK answered the question by leaving no doubt that before his assassination Kennedy had determined to quit Vietnam. Yet the historical record offers a much more complex answer. In this fresh look at the archival evidence, noted scholars take up the challenge to provide us with their conclusions about the early decisions that put the United States on the path to the greatest American tragedy since the Civil War. The tensions and turmoil that accompanied those decisions reveal the American presidency at the center of a storm of conflicting advice. The book is divided into four sections. Part one delves into the political context in which the early decisions were made, while part two considers the military context. Part three raises the intriguing questions of Kennedy's and Johnson's roles in the conflict, particularly the thorny issue of whether Kennedy did, in fact, intend to withdraw from Vietnam and whether Johnson reversed that policy. Part four reveals an uncanny parallel between early Soviet policy toward Hanoi and U.S. policy toward Saigon.